(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: the Zika virus is a flavivirus that is transmitted by the bite of the Aedes aegypti mosquito, which is also the vector that transmits the Dengue and Chicungunya virus. It was first identified in Uganda in 1947 and the first case in humans was diagnosed in 1952 in Tanzania. METHODS: a Cochrane systematic review was conducted in the second semester of 2018, following the PICO model for question formulation and search strategy. The PICO model proposal is used in evidence-based medical care and its ontology defines the criteria of the terminology to be used. RESULTS: the association of the Zika virus with microcephaly and other severe neurological alterations was reported mainly in Brazil in 2015. ANALYSIS AND DISCUSSION: in the field of health, the importance of Zika lies in the relationship it has with other viruses of the flavivirus genus that produce diseases such as dengue, chikunguya, yellow fever, West Nile fever and Japanese encephalitis. Hence, the special attention that the subject has throughout the world, given that diseases can spread to the entire globe, and Zika virus infection is no exception. CONCLUSIONS: scientific evidence demonstrates the relationship between Zika virus infection and congenital malformations of the central nervous system of newborns, by confirming the presence of the virus in samples of placental tissue and amniotic fluid